Thin Film Metal-Oxides Fundamentals and Applications in Electronics and Energy - Ramanathan, Shriram; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2010)
Thin Film Metal-Oxides provides a representative account of the fundamental structure-property relations in oxide thin films. Functional properties of thin film oxides are discussed in the context of applications in emerging electronics and renewable energy technologies. Readers will find a detailed description of deposition and characterization of metal oxide thin films, theoretical treatment of select properties and their functional performance in solid state devices, from leading researchers. Scientists and engineers involved with oxide semiconductors, electronic materials and alternative energy will find Thin Film Metal-Oxides a useful reference. .
In Situ Synchrotron Characterization of Complex Oxide Heterostructures -- Metal-Insulator Transition in Thin Film Vanadium Dioxide -- Novel Magnetic Oxide Thin Films -- Bipolar Resistive Switching in Oxides for Memory Applications -- Complex Oxide Schottky Junctions -- Theory of Ferroelectricity and Size Effects in Thin Films -- High-T c Superconducting Thin- and Thick-Film–Based Coated Conductors for Energy Applications -- Mesostructured Thin Film Oxides -- Applications of Thin Film Oxides in Catalysis -- Design of Heterogeneous Catalysts and the Application to the Oxygen Reduction Reaction.
Keywords: Materials—Surfaces.; Thin films; Energy systems; Energy; Surfaces and Interfaces, Thin Films; Energy Systems; Energy, general